THE CORRELATION OF TRANSAMINASES AND LIVER DISEASES - Alfian Juatmadja, Bastianus; Sutirta Yasa, I Wayan Putu; Rasmika dewi, DAP; Satriyasa, Bagus Komang (Bali Journal of Medical and Health Sciences; vol 1no1 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 The s y m pto m s of l i v e r d i s ea s e s a re v e r y div e r g i n g, f r om the m i ld one t i ll the s e v e re on e . S ometi m e s we m a y find that s e v e r e h e a rt di s o r d e rs but the s y mp t oms a re too l e ss. W e n ee d some too l s to make a g ood di a g nosi s . W e c a n not on l y use a g ood a n a mnesis, but a lso h a ve to use g ood p h y sic a l e x a m i n a t i on a nd the other support tes t . T ra n s a m i n a se a lso ca l l e d a m i notr a nsf e r a se. This a m i notr a nsf e r a s e c a ta l y z e s the tr a n s f e r of the a m i no g r oup ( ? N H 2 ) of a n a m i no ac id to a ca rbo n y l c ompoun d . The l i v e r c ontains spe c ific tr a n s a m inas e s for the tr a nsf e r of a n a m i no g r o up f r om g lu t a m i c ac id t o ?- k e to ac ids that c o r respond to most of the other a m i no a c ids. O ther tr a nsamina s e s c a ta l y z e r e ac t i ons in whi c h a n a m i no g r oup is tr a nsf e r r e d f rom g lu t a m i c ac id to other c ompou n ds. T ra nsaminat i on is one of the p r incip a l me c h a nis m s for t h e fo r mation of n e c e ssa r y a m ino ac i d s in the met a b o l i sm of p r oteins. T ra nsaminase a s a si g n to c e ll d a m a ge m a y d iv i d e d in t o S e rum Glu t a m i c O x a loc e t i c T ra nsaminase ( S G O T ) , S e rum Glutamic P y r uvic T ra nsaminase ( S GPT), a nd L ac t i c D e h y d r o g e n a se ( L DH ) . G a m m a G T a nd a l k a li fos fa ta s e c o r re l a te with c holestasis. Chol i n e str a se c o r r e late w i t h l i v e r s y nthesis c a p ac i t y . /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}